Worm control for small ruminants in Southeast Asia - Sani, R.A.; Gray, G.D. (Australian Centre for International Agricultural Research, 2004)
The focus of this volume is on small ruminant production, the effects that nematode parasites have on their productivity and ways of overcoming these effects. In some chapters, avoidance takes on more significance than direct confrontation. This volume is arranged in two sections. The first section describes some advances in techniques and in the thinking behind worm control for smallholders in the humid tropics. Questions addressed include how to estimate the costs and benefits of control measures, how to make best use of genetic variation in resistance, how to use computerised tools in assessing control interventions, and how to use participatory approaches to help in devising sustainable control options. The second section includes separate chapters on published, grey and some previously unpublished information from Indonesia, Philippines, Nepal, Malaysia, Thailand, Fiji and Papua New Guinea. Vietnam, Lao and Cambodia are included in a single chapter as there has been little work on small ruminants in these countries.